A case of ovarian serous borderline tumors with normal ovarian findings on preoperative imaging - Sato, Shimpei; Ogura, Jumpei; Nakagami, Ayaka; Koshida, Yuichiro; Sadamoto, Satoko; Kasuga, Maya; Kanamoto, Naokazu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian serous borderline tumors (SBTs) are typically diagnosed through imaging techniques such as ultrasound and magnetic resonance imaging (MRI); however, diagnosis can be challenging when the tumor exhibits unusual growth patterns or is of small size. We report the case of a 55-year-old woman in whom bilateral SBTs were discovered during surgery, although preoperative imaging showed no ovarian abnormalities. The patient underwent laparoscopic total hysterectomy and bilateral adnexectomy for uterine fibroids. Preoperative MRI and transvaginal ultrasound did not reveal any ovarian abnormalities, but during laparoscopic surgery, small nodules growing outward were observed on both ovaries. Pathological examination led to the diagnosis of a serous borderline tumor with micropapillary pattern (SBT-MP). This case highlights the limitations of preoperative imaging in detecting small serous borderline tumors with surface papillary growth, as no abnormalities were observed preoperatively despite bilateral ovarian involvement. When an ovarian tumor exhibiting surface growth is identified during surgery, even if it is too small to be detected preoperatively, it is crucial to consider the possibility of a borderline tumor. In such cases, it is essential to perform pathological examination, including intraoperative frozen section analysis, and conduct a thorough macroscopic inspection of the abdominal cavity.